Correlation of anxiety and depression with socio-economic status among caregivers of children admitted at Dhulikhel Hospital: A cross-sectional study - Panthee, Anjana; Kaiti, Soni (Journal of Chitwan Medical College, 2026)
Introduction: The paediatric ward is a highly stressful environment affecting economic and social productivity of caregivers. Evaluating anxiety and depression among caregivers, along with their socioeconomic status, is vital for early detection of psychiatric morbidity. This study aimed to assess anxiety, depression, and socioeconomic status, and examine their correlation among caregivers of hospitalized children. Methods: A cross-sectional study was conducted at Dhulikhel Hospital, Nepal, in paediatric wards, PICU, and PHDU from Jun 2023 to Jan 2024. Adult primary caregivers aged 18–60 years, having children aged 6 weeks to 16 years hospitalized for ≥7 days were recruited. Data collection tools included HADS Nepali and Modified Kuppuswamy Socioeconomic Scale. Ethical approval was obtained from IRC. Data were analysed using SPSS version 27 with Pearson correlation test, and p<0.05 was considered significant. Results: Out of a total of 78 caregivers, mean age was 31.35±7.39 years; 60(77%) were female. Anxiety was present in 40(51%) and depression in 23(30%) participants. Socioeconomic status showed 46(59%) from middle and 30(38%) from lower class. Correlation between anxiety, depression, and socioeconomic status was not statistically significant (r=-0.138, p=0.227). Conclusions: Anxiety and depression were prevalent among caregivers of hospitalized children. A negative correlation with socioeconomic status was observed, which is clinically meaningful despite lack of statistical significance. Early screening and psychological support for at-risk caregivers is recommended.